2016
DOI: 10.1159/000446869
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Plays an Important Role in the Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells into Cardiomyocytes

Abstract: Objectives: Accumulating evidence has demonstrated that bone marrow-derived mesenchymal stem cells (BMSCs) may transdifferentiate into cardiomyocytes, making BMSCs a promising source of cardiomyocytes for transplantation. However, little is known about the molecular mechanisms underlying myogenic conversion of BMSCs. Methods: This study was designed to investigate the functional role of caveolin-1 in the cardiomyocyte differentiation of BMSCs and to explore the potential underlying molecular mechanisms. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Recent studies are attempting to discover stem cells with higher potential for the treatment of MI (Ding et al, 2015[6]). The safety and efficiency of BMSCs to treat MI have been shown in animal models (Chen et al, 2017[5]). BMSCs transplantation has demonstrated advantageous results regardless of their possible therapeutic effects; either by differentiation into cardiomyocyte-like cells or acting via paracrine signaling (e.g., by increasing angiogenesis) (He et al, 2010[11]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies are attempting to discover stem cells with higher potential for the treatment of MI (Ding et al, 2015[6]). The safety and efficiency of BMSCs to treat MI have been shown in animal models (Chen et al, 2017[5]). BMSCs transplantation has demonstrated advantageous results regardless of their possible therapeutic effects; either by differentiation into cardiomyocyte-like cells or acting via paracrine signaling (e.g., by increasing angiogenesis) (He et al, 2010[11]).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that some kinds of stem cells may be suitable for cell-based therapy in heart failure, bone marrow-derived stromal cells (BMSCs) are appealing since they can be simply extracted and expanded in culture (Antonitsis et al, 2007[1]). It has been shown that BMSC-based therapy and tissue engineering for heart failure is feasible and safe (Chen et al, 2017[5]). In addition, BMSCs were shown to have some other vital biological advantages including angiogenesis, immune modulation, and anti-apoptotic activities (Chen et al, 2017[5]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicate that Caveolin-1 could play an important role in proliferation and differentiation of BMSCs [ 121 123 ], but the role of Caveolin-1 in cardiomyocyte differentiation of BMSCs remains unknown. Chen et al [ 124 ] find that both mRNA and protein levels of Caveolin-1 are increased in 5-aza-treated BMSCs, suggesting that Caveolin-1 may be involved in the differentiation of BMSCs into cardiomyocytes. To further explore the role of Caveolin-1 in BMSC differentiation, Caveolin-1 siRNA is used.…”
Section: Othersmentioning
confidence: 99%
“…Bone marrow-derived mesenchymal stem cells (BMSCs) are pluripotent stem cells derived from bone marrow, with the potential of self-renewal and differentiation into various cell types, such as adipocytes, cardiomyocytes ( 10 ), endotheliocytes and neurons ( 11 ). BMSCs can perceive damage signals and migrate into the damaged area.…”
Section: Introductionmentioning
confidence: 99%